Setlokwa dialect in Sepedi home Language essay writing in grade 10, Sekgosese Circuit, Capricorn South District Limpopo Province, South Africa - Maredi, Zelda Mamotsumi (My University, 2024)
This study aimed to explore the effect of Setlokwa Dialect on Sepedi Home Language Essay Writing in Grade 10, Sekgosese Circuit, Capricorn South District Limpopo Province, South Africa. It explored and identified the problems faced by Setlokwa speakers (learners) when writing certain words in formal Sepedi and traced the relationship between dialects and formal language. Overall, the study explored the effects of Setlokwa when writing essay in grade 10 Sepedi Home language, and suggested ways to include the dialects in the formal writing of Sepedi in the classroom. The Grade 10 learners at the Sekgosese Circuit, Capricorn South District, find it difficult to write in Sepedi as an official home language at school. They commit spelling errors that cost them more marks during examinations. Such errors are basically visible when they write Sepedi essays or Paper 3 Examinations. As such, the study was conducted to assess how the Sepedi Home Language curriculum is implemented in the classroom to address and respond to essay writing issues in grade 10 affected by Setlokwa as dialect language. This study employed a qualitative research method and sampled one secondary school. Data were gathered through unstructured interviews and document analysis. The study included teachers and Grade 10 students as participants. The study was informed by the constructivism theory. As this theory believe that learning is affected by the context in which an idea is taught by the student’s beliefs and attitudes , in this case grade 10 learners affected by the dialect language within their context in relation to Sepedi Home Language.
Thesis (M.Ed. (Language Education)) -- University of Limpopo, 2024
Keywords: Essay writing; Dialect; Sepedi home language; Northern Sotho language -- South Africa -- Limpopo; Essays; Northern Sotho essays; Northern Sotho language -- Study and teaching